Pembelajaran dengan Pendekatan TaRL untuk Meningkatkan Minat dan Hasil Belajar Matematika Peserta Didik - Tanthowi Jauhari; Abdul Haris Rosyidi; Amik Sunarlijah (Jurnal PTK dan Pendidikan, 2023)
Abstract: This research was motivated by the low interest and learning outcomes of class VIII-F students of SMP Negeri 54 Surabaya. Learning that is not in accordance with the abilities of students can cause students to be less active and experience a decrease in interest in learning. Low interest in learning can have an impact on low learning outcomes. Learning with the Teaching at the Right Level (TaRL) approach which does not refer to the class level can facilitate various characteristics of students. The research conducted in these 2 cycles aims to increase interest in and results in learning mathematics through the TaRL approach. TaRL emphasizes teachers to give students different treatment so that students' learning abilities and interests can develop according to their respective levels of development. Data on interest in learning were collected through questionnaires and data on learning outcomes through written tests, both of which were analyzed quantitatively. The indicator of the success of this research is that the percentage of students' interest in learning is included in the "adequate" criteria and students get a minimum score of 80 on the learning outcomes test with a completeness percentage of >30%. The results showed that the average percentage of interest in learning increased 16% from 50% (low) in cycle I to 66% (enough) in cycle II. In the aspect of learning outcomes indicated by an increase in the percentage of completeness of 40.7% from 9.3% in cycle I to 50% in cycle II. The average student score increased by 16 points from 63 points in cycle I to 79 points in cycle II.Keywords: Learning Interest, Learning Outcome, TaRL Abstrak: Penelitian ini dilatarbelakangi oleh rendahnya minat dan hasil belajar peserta didik kelas VIII-F SMP Negeri 54 Surabaya. Pembelajaran yang tidak sesuai dengan kemampuan peserta didik dapat menyebabkan peserta didik kurang aktif dan mengalami penurunan minat belajar. Minat belajar yang rendah dapat berdampak pada hasil belajar yang rendah. Pembelajaran dengan pendekatan Teaching at the Right Level (TaRL) yang tidak mengacu pada tingkat kelas dapat memfasilitasi berbagai karakteristik peserta didik. Penelitian yang dilakukan dalam 2 siklus ini bertujuan meningkatkan minat dan hasil belajar matematika melalui pendekatan TaRL. TaRL menekankan guru untuk memberikan peserta didik perlakuan yang berbeda agar kemampuan dan minat belajar peserta didik dapat berkembang sesuai tingkat perkembangan masing-masing. Data minat belajar dikumpulkan melalui lembar angket dan data hasil belajar melalui tes tulis dengan keduanya dianalisis secara kuantitatif. Indikator keberhasilan penelitian ini yaitu persentase minat belajar peserta didik termasuk dalam kriteria “cukup” dan peserta didik memperoleh nilai minimal 80 pada tes hasil belajar dengan persentase ketuntasan >30%. Hasil penelitian menunjukkan bahwa rerata persentase minat belajar meningkat 16% dari 50% (kurang) pada siklus I menjadi 66% (cukup) pada siklus II. Pada aspek hasil belajar ditunjukkan dengan adanya peningkatan persentase ketuntasan sebesar 40,7% dari 9,3% pada siklus I menjadi 50% pada siklus II. Rerata nilai peserta didik mengalami peningkatan 16 poin dari 63 poin pada siklus I menjadi 79 poin pada siklus II.Kata Kunci: Hasil Belajar, Minat Belajar, TaRL